P‐121: Polymer‐Stabilized Blue‐Phase Liquid Crystal Display using Distributed Floating Electrode. Issue 1 (May 2016) - Chang, Yu-Chuan; Wei, Shih-Hsien; Chang, Chia-Liang; Choi, Wing-Kit
Abstract : Results are presented for a new electrode design for a Blue Phase display based on floating electrode. We name it "distributed floating electrode design". In this new design, we can use less area of floating electrode while still achieving the similar increase of the overall light transmission. This new design may have the potential to help reduce the image sticking problem that may be caused by the use of floating electrode.